Extension of Fogg Behaviour Model: Behavioural Intention to Enrol in Online Learning Courses, An Indian Perspective - Kshitiz Gupta, Dr. V. V. Ravi Kumar (International Journal of Advanced Science and Technology, 2020)
India has seen a massive expansion of the network and communication technology over the past few years. The increased penetration and adoption of internet services throughout the country has led to a spurt in the consumption of data. This is due to affordable handsets, cheap data plans, and the increasing popularity of videos. India, being a diverse and culturally rich country, the minds behind creating online content are increasingly focussing on vernacular languages to make their content adaptable and relatable to a wider audience. All such steps have opened new avenues for people to gain knowledge through the internet at the comfort of their homes. This has given rise to major online learning platforms such as Coursera, Udemy, edX, Byju’s, Udacity etc. Even the video-sharing website YouTube contains thousands of ‘How to’ videos using which consumers learn and grow. Several educators have also launched their channels on YouTube where they share content on diversified subjects using which anyone can gain knowledge. The popularity of such channels has increased multi-folds in recent years that YouTube introduced paid subscriptions to help content creators monetize their channels. This study aims to find out the underlying factors which lead to the behavioural intention of consumers to enrol in online learning courses. The study involves the extension of Fogg Behaviour Model to identify key constructs which lead to the final dependent variable of behavioural Intention which is a prime construct of the TPB (Theory of Planned Behaviour). The key constructs identified are motivation, ability, trigger, perceived value and social influence which affect the Behavioural Intention to enrol in online learning courses.